Analysis of the Effectiveness of Employee Training and Development In Islamic Boarding Schools in Improving the Quality of Education - Rizqi Syaroh Amaliyah (Jurnal Impresi Indonesia, 2024)
Traditional educational institutions such as Islamic boarding schools combine a curriculum that includes religious subjects, such as tafsir, hadith, and fiqh, with general subjects, such as math, science, and languages. This study aims to analyze the effectiveness of employee training and development in boarding schools in improving the quality of education. Using a qualitative approach, this study examines various training and development programs implemented in several Islamic boarding schools, as well as their impact on the competence of teaching and education personnel. Data were collected through literature studies and analyzed to identify the relationship between training programs and improved performance and teaching quality. The results showed that systematic and continuous training significantly improved the skills and knowledge of the educators, which contributed to a more effective and adaptive teaching and learning process. In addition, continuous professional development helps educators in pesantren to remain relevant to developments in teaching methodologies and educational technology. These findings confirm the importance of investing in staff training and development as a key strategy to improve the quality of education in pesantren.